Argentina : First Review Under the Stand-By Arrangement and Exchange System. (IMF Staff Country Reports; Country Report, 2003)
The transitional program is broadly on track and quantitative program targets have been met, but structural reforms have been delayed. There are still risks to revenues and expenditures from possible judicial decisions, and the fiscal program may need to be adapted for changes in the macroeconomic framework. Monetary policy continues to face significant uncertainties, and priority needs to be given to providing a predictable regulatory framework for the banking system. Policy preparation can facilitate the transition to the new government.